LO15: The incidence of intracranial bleeding following a fall on level ground in geriatric patients. (May 2019) - de Wit, K.; Merali, Z.; Kagoma, Y.; Mercier, É.
Abstract : Introduction : Falls are a common presentation to the emergency department among geriatric patients. The incidence of intracranial bleeding following a fall is unclear and approach to ordering a CT head scan is not standardized. The aim of this systematic review and meta-analysis was to establish the incidence of intracranial bleeding after a fall in geriatric patients.Methods : The systematic review was registered in PROSPERO. Two authors independently searched Medline and EMBASE (OVID interface) from conception till 20th June 2018. The search combined multiple MESH terms and text words for [falls], [elderly] and [brain injury]. The search was repeated in Google Scholar and recent conference abstracts were reviewed. Studies were included if > 80% of the included patients were > 65 years who presented to the emergency department after a fall on level ground. We excluded studies enrolling select populations (for example trauma team activation, neurosurgical patients or only anticoagulated patients). There were no language restrictions. The random effects model was used to perform a meta-analysis on the incidence of intracranial bleeding in geriatric patients after a fall on level ground.Results : From the 7, 043 titles and abstracts, 175 full articles were reviewed and 7 studies, including 6758 patients, were included in the analysis. 2/7 studies were prospective. The studies varied in their inclusion criteria with 3/7 studies only including patients with normal neurological testing. Most retrospective studies included patients if they had a CT head scan. Neither prospective study imaged all patients but both followed the patients for a delayed diagnosis of intracranial bleeding. Risk of bias was moderate or high for the majority of studies. The random effects pooled incidence of intracranial bleeding was 5.2% (95% CI 2.8 – 8.2%), I2 96%.Conclusion : Around 1 in 20 geriatric patients who present to the emergency department after a fall have intracranial bleeding. This point estimate can be used to calculate sample size requirements for future studies on intracranial bleeding in this population.